Comparative Statics and the Logic of Economic Maximizing - Samuelson, Paul A. (Review of Economic Studies, 1946)
Journal Article Comparative Statics and the Logic of Economic Maximizing Get access Paul A. Samuelson Paul A. Samuelson Cambridge, Massachusetts Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 14, Issue 1, 1946, Pages 41–43, https://doi.org/10.2307/2295756 Published: 01 April 1946